MAHASISWA DAN MALARI DI JAKARTA: TELAAH PERILAKU KOLEKTIF MAHASISWA INDONESIA 1973-1974 - Yohanes de Britto Wirajati (Fakultas Ilmu Budaya universitas Hasanuddin, 2018)
By focusing on the Malari Incident, this article aims at understanding the formation process of student network in 1973-1974, the actions initiated by the student movements, and the actions by the governments to weaken the influence of the political power of the network and the student actions of 197-1974. The method being employed in the article is library research and the analysis is done through heuristic work. In this heuristic work all the sources collected are compared and interpreted until a conclusion is reached. The results of the research show that the student network in 1973-1974 was grounded on the conditions of widespread foreign investment. The student network was created through various discussion activities and touring to various campuses. In the Malari Incident it can be seen there were initiation, independence and strong solidarity among students within the movement in challenging the state authority of the time.